Clinical, endoscopic and histological correlation and measures of association in ulcerative colitis. Issue 11 (22nd December 2017) - Fluxá, Daniela; Simian, Daniela; Flores, Lilian; Ibáñez, Patricio; Lubascher, Jaime; Figueroa, Carolina; Kronberg, Udo; Pizarro, Gonzalo; Castro, Magdalena; Piottante, Antonio; Vial, María T.; Quera, Rodrigo
Abstract : OBJECTIVE: To determine the correlation between clinical, fecal, endoscopic and histological activity in patients with ulcerative colitis (UC). METHODS: A correlational cross‐sectional analysis was performed in patients with UC who underwent colonoscopy between February and December 2016. Clinical, endoscopic, fecal and histological activities were determined using the partial Mayo subscore, Mayo endoscopic subscore and modified Mayo endoscopic subscore, fecal calprotectin and Geboes score and the presence of basal plasmacytosis, respectively. Scores were analyzed using Spearman's rank correlation test. To determine the association between scores and some clinical variables and active UC, univariate and multivariate logistic regressions were used. RESULTS: Altogether 105 procedures (93 patients) were included. In 64.8% of the procedures, the mucosa was inflamed; however, 14.7% did not show histological inflammation. Endoscopic remission was observed in the other 35.2% of procedures; however, in biopsies 21.6% exhibited histological inflammation. Mayo endoscopic subscore and modified Mayo endoscopic score were well correlated but were only moderately correlated with clinical and histological scores. Furthermore, there was a moderate correlation between Mayo endoscopic score and Geboes score. Conversely, histological scores were poorly correlated with partial Mayo score. In multivariate analysis, Geboes score and basal plasmacytosis were predictive of active disease (OR 3.505, 95% CI 1.544–7.959 and OR 3.240, 95% CI 1.123–9.349, respectively), whereas biological therapy was found to be protective against UC (OR 0.021, 95% CI 0.000–0.641). CONCLUSION: Clinical, endoscopic and histological activities were moderately correlated, while Geboes score and basal plasmacytosis were predictive of endoscopically active UC.